Letter from William Faber to James Curtis Booth, July 7, 1850 - Faber, William (1850)
Request for analysis of a sample of ore.
Keywords: Booth, James Curtis, 1810-1888; Ores--Sampling and estimation; Ores; Mines and mineral resources